(untitled) (Bangladesh Journal of Psychiatry, 2017)
Mental health is the most neglected and stigmatized branch of medical science in Bangladesh. Attitudes towards psychiatry are an important determination for selection of the subject as career by the undergraduate medical students. The objective of this study was to determine the attitudes of undergraduate medical students towards psychiatry and related factors. It was across sectional study conducted from May 2013 to September 2013 among 1st and 5th year medical students of Rajshahi Medical College, Rajshashi and Shaheed Shahrawardi Medical College, Dhaka. Results showed that only 2.6% of 5th year medical students wanted to be specialized in psychiatry and none of 1st year medical students wanted to be specialized in psychiatry. All of them (100% and 98.7%) agreed with the statement that psychiatric research has made good strides in advancing care of major mental disorder and majority students of both groups were (96% and 86.6% respectively) with the statement that psychiatry was a rapidly expanding frontier of medicine. Around two-third of the students (79.3% and 82.7% respectively) perceived psychiatric treatment as being helpful. Fifty nine (76.6%) of 5th year students and forty one (55.7%) of 1st year students did not agree that psychiatrists frequently abuse their legal power to hospitalize patients against their will. Positive opinions on attitudes of undergraduate medical students towards psychiatry became strengthen further following exposure to psychiatry lectures and clerkship in psychiatry ward. Bang J Psychiatry Dec 2014; 28(2): 45-49